Relation of Facial Expressions and Student Learning Outcomes in Face Recognition-Based Online Learning - Hamzarudin Hikmatiar; Nursina Sya'bania; Berlian Hamsa (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2024)
This research was conducted to determine the relationship between facial expressions and student learning outcomes based on face recognition. The applied learning is online, with nine respondents participating in statistics lectures. This type of research is quantitative research with inferential statistical analysis; the software used to detect facial expressions is LOBE software, while the data collection on learning outcomes uses multiple choice questions as many as ten. Based on the research results, there is a relationship between facial expressions and student learning outcomes, which are carried out through the person correlation test with a significance of less than 0.05, namely 0.001. The level of the relationship between the two is a perfect correlation based on the correlation guide table, which is equal to 0.895.